Aberrant myelination of the cingulum and Schneiderian delusions in schizophrenia: a 7T magnetization transfer study. Issue 11 (19th September 2018) - Palaniyappan, Lena; Al-Radaideh, Ali; Mougin, Olivier; Das, Tushar; Gowland, Penny; Liddle, Peter F.
Abstract: Background: The structural integrity of the anterior cingulum has been repeatedly observed to be abnormal in patients with schizophrenia. More recently, aberrant myelination of frontal fasciculi, especially, cingulum has been proposed to underlie delayed corollary discharges that can affect sense of agency and contribute to delusions of control (Schneiderian delusions). Using the magnetization transfer phenomenon at an ultra-high field 7T MRI, we investigated the putative myelin content of cingulum bundle in patients with schizophrenia. Methods: Seventeen clinically stable patients with schizophrenia and 20 controls were recruited for this 7T MRI study. We used a region-of-interest method and extracted magnetization transfer ratio (MTR) from left and right dorsal cingulum bundles and estimated patients v. controls differences. We also related the cingulum MTR values to the severity of Schneiderian delusions. Results: Patients had a significant reduction in the MTR, indicating reduced myelin content, in the cingulum bundle (right cingulum Hedges' g = 0.91; left cingulum g = 0.03). The reduced MTR of left cingulum was associated with higher severity of Schneiderian delusions ( τ = −0.45, p = 0.026) but no such relationship was seen for the right cingulum MTR ( τ = −0.136, p = 0.50) among patients. The association between the left cingulum MTR and Schneiderian delusions was not explained by the presence of other delusions, hallucinations, disorganization or negative symptoms. Conclusions: Dysmyelination of the cingulum bundle is seen in a subgroup of patients with schizophrenia and may be involved in the mechanism of Schneiderian delusions.